2017
DOI: 10.1002/col.22188
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in color preference across cultures: An archetypal pattern modulated by a female cultural stereotype

Abstract: A gender difference in color preference among British participants has been repeatedly reported, in which both males and females show a preference for blue-green colors, while females express an additional preference for pink-purple colors. To investigate the robustness of gender difference in color preference in a different culture, we tested 81 young adult Indians from a school of design and compared them to 80 young British students in Psychology. The 35-item International Personality Item Pool (IPIP) and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
30
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 26 publications
(57 reference statements)
5
30
1
1
Order By: Relevance
“…In addition to these gender differences, we observed that blue was the most common favourite colour by both genders of all ages. Hence, despite the popular notion that blue is for boys (Cunningham & Macrae, 2011), our and other empirical studies indicate that blue (or blue-green, which was included in the blue hue category in the current study) is the most popular hue for both genders when genders were considered together (Eysenck, 1941;Hemphill, 1996;Jonauskaite et al, 2016;Palmer & Schloss, 2010) or separately (Bonnardel et al, 2017;Ou et al, 2004). Other developmental studies have also shown that blue is a liked colour by boys and girls, with few gender differences (Chiu et al, 2006;Terwogt & Hoeksma, 1995).…”
Section: Discussioncontrasting
confidence: 76%
See 4 more Smart Citations
“…In addition to these gender differences, we observed that blue was the most common favourite colour by both genders of all ages. Hence, despite the popular notion that blue is for boys (Cunningham & Macrae, 2011), our and other empirical studies indicate that blue (or blue-green, which was included in the blue hue category in the current study) is the most popular hue for both genders when genders were considered together (Eysenck, 1941;Hemphill, 1996;Jonauskaite et al, 2016;Palmer & Schloss, 2010) or separately (Bonnardel et al, 2017;Ou et al, 2004). Other developmental studies have also shown that blue is a liked colour by boys and girls, with few gender differences (Chiu et al, 2006;Terwogt & Hoeksma, 1995).…”
Section: Discussioncontrasting
confidence: 76%
“…In particular, we hypothesised that women would show a tendency to select pinkish-reddish hues, whereas men would not select them. We also predicted that blue would be equally liked by men and women (e.g., Bonnardel et al, 2017;Eysenck, 1941). One important result from previous literature was that the gender difference in preference for pink was higher in girls than in women.…”
mentioning
confidence: 74%
See 3 more Smart Citations